Preparation and evaluation of oral controlled‐release cilostazol formulation: pharmacokinetics and antithrombotic efficacy in dogs and healthy male Korean participants. (20th February 2014) - Shin, Kwang‐Hyun; Yoon, Goo; Yoon, In‐Soo; Park, Jin Woo
Abstract Objectives To prepare oral controlled‐release cilostazol formulations and evaluate their pharmacokinetics and pharmacodynamics in dogs and humans compared with a commercial twice‐daily immediate‐release formulation (Pletal), thereby showing the potential for the development of an improved once‐daily cilostazol formulation. Methods Six different controlled‐release preparations were formulated using a micronized cilostazol, solubilizer/absorption enhancer and erodible hydrogel. In‐vitro drug release profiles were tailored by varying hydrogel viscosity. Pharmacokinetics and pharmacodynamic (antithrombotic) efficacy were evaluated in beagle dog model of arterial thrombosis. Finally, their pharmacokinetics and pharmacodynamics were also evaluated in healthy human volunteers after single and multiple oral administrations. Key findings Hydrogel viscosity‐dependent sustained drug release profiles were observed with zero‐order release kinetics during 8–12 h. In dogs and humans, compared with Pletal, prolonged drug absorption profiles were observed in the two controlled‐release formulations studied. In dogs, the controlled‐release formulations showed greater antithrombotic efficacy than twice‐daily Pletal. In humans, the antithrombotic efficacy of the selected once‐daily cilostazol formulation was equivalent to that of twice‐daily Pletal after single and multiple administrations. Conclusions The prepared oral controlled‐release cilostazol formulation may provide prolonged drug absorption and sufficient therapeutic efficacy, potentially serving as an oral once‐daily cilostazol formulation to improve patient compliance.